1989
DOI: 10.1038/ki.1989.242
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acid dietary supplementation in systemic lupus erythematosus

Abstract: The effect of dietary fish oil (Omega-3 fatty acids--eicosapentenoic acid [EPA] and docosahexaenoic acid [DHA] on several mechanisms involved in immune, inflammatory and atherosclerotic vascular disease was determined in 12 subjects with systemic lupus erythematosus (SLE) and nephritis. These out-patients supplemented their usual diet for five weeks with daily doses of 6 g of fish oil, followed by a five-week washout period, then five weeks of 18 g of fish oil daily. The platelet EPA content rose six-fold with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
4

Year Published

1991
1991
2001
2001

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 50 publications
0
37
0
4
Order By: Relevance
“…A National Institutes of Health funded, controlled, and double-blinded study is being conducted by the Southwest Pediatric Nephrology Study Group in children to test the efficacy of this medication in IgA nephropathy. Polyunsaturated fatty acid supplementation was used in lupus nephropathy, but with ambiguous results, by Clark et al [173]. Negative results were obtained by Westberg and Tarkowski [174]as well as in a larger study by Clark et al [175].…”
Section: Treatmentmentioning
confidence: 87%
“…A National Institutes of Health funded, controlled, and double-blinded study is being conducted by the Southwest Pediatric Nephrology Study Group in children to test the efficacy of this medication in IgA nephropathy. Polyunsaturated fatty acid supplementation was used in lupus nephropathy, but with ambiguous results, by Clark et al [173]. Negative results were obtained by Westberg and Tarkowski [174]as well as in a larger study by Clark et al [175].…”
Section: Treatmentmentioning
confidence: 87%
“…Other inflammatory and autoimmune diseases which have been subject to trials of n-3 PUFA supplementation include bronchial asthma (Parm et al 1988;Picado et al 1988), atopic dermatitis (Bjorneboe et al 1987;, systemic lupus erythematosus (Clark et al 1989;Westberg & Tarkowski, 1990) and ulcerative colitis (Hawthorne et al 1992). Das (1994) reported that long-term (many months to several years) consumption of n-3 PUFA led to very marked reduction in the symptoms of systemic lupus erythematosus.…”
Section: Clinical Aspects O F Immunomodulatton B Y N -3 Polyunsaturatmentioning
confidence: 99%
“…However, several interest ing effects have been noted. Clark et al [51] treated 12 patients with systemic lupus erythematosus and associat ed nephritis with omega-3 fatty acid supplementation of their regular diets. In this short-term study, no effect on albuminuria or kidney function was seen.…”
Section: Omega-3 Fatty Acid (Fish Oil) Supplementationmentioning
confidence: 99%